2020
DOI: 10.1101/2020.06.06.138339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Whole Genome Amplification and Sequencing for Effective Population-Based Surveillance and Control of Viral Transmission

Abstract: These authors contributed equally to this work. Abstract BackgroundWith the gradual reopening of economies and resuming social life, robust surveillance mechanisms should be implemented to control the ongoing COVID-19 pandemic. Unlike RT-PCR, SARS-CoV-2 Whole Genome Sequencing (cWGS) has the added advantage of identifying cryptic origins of the virus, and the extent of community-based transmissions versus new viral introductions, which can in turn influence public health policy decisions.However, practical con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Libraries were sequenced using the NovaSeq SP Reagent kit (2 X 150 cycles) from Illumina (San Diego, CA, USA). Sample L5630 underwent a target enrichment approach where double stranded DNA (synthesized using the QuantiTect Reverse Transcription Kit from Qiagen, Hilden, Germany) was amplified using 26 overlapping primer sets covering most of the SARS-CoV-2 genome as recently described by our group 9 . PCR products were then sheared by ultra-sonication (Covaris LE220-plus series, MA, USA) and prepared for sequencing using the SureSelectXT Library Preparation kit (Agilent, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Libraries were sequenced using the NovaSeq SP Reagent kit (2 X 150 cycles) from Illumina (San Diego, CA, USA). Sample L5630 underwent a target enrichment approach where double stranded DNA (synthesized using the QuantiTect Reverse Transcription Kit from Qiagen, Hilden, Germany) was amplified using 26 overlapping primer sets covering most of the SARS-CoV-2 genome as recently described by our group 9 . PCR products were then sheared by ultra-sonication (Covaris LE220-plus series, MA, USA) and prepared for sequencing using the SureSelectXT Library Preparation kit (Agilent, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…We found that the transcriptome in HAE-ALI reflects more closely the viral transcriptome in the airways of COVID-19 patients, supporting that HAE-ALI is a physiologically relevant in vitro culture to study SARS-CoV-2. Neither RNA-seq data of clinical SARS-CoV-2 positive nasopharyngeal specimens nor RNA-seq of SARS-CoV-2 infected HAE-ALI showed the 5'-leader sequence read peak (38,39). In SARS-CoV-2 infected Vero-E6 cells, N sgRNAs accounted for up to 69% in total viral RNA transcripts, and S sgRNAs accounted for 8% of the total junction-spanning reads (15) (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…As the COVID-19 pandemic continues to rage, the use of genomic surveillance to monitor SARS-CoV-2 outbreaks in healthcare settings as well as in farms where thousands of potentially susceptible animals live in close proximity has become increasingly important [4][5][6] . Moreover, with the appearance of new lineages with potentially higher infectivity and/or pathogenicity, such as the recently emerged UK lineage 18 , there is an urgent need for streamlined and cost-effective approaches that could be deployed for sequencing thousands of viral samples per week.…”
Section: Discussionmentioning
confidence: 99%